Knowledge, practices and precaution regarding COVID-19 among the residents of Kolkata city, West Bengal, India - Mukherjee, Nirmalya; Mahapatra, Biswajit; Chowdhury, Srijita; Bhattacharya, Paramita; Khatoon, Sajda (International Journal of Research in Medical Sciences, 2022)
Background: Corona virus disease 2019 (COVID-19) has been declared a global public health emergency affecting thousands of people across the world. The knowledge, attitude and practice related to the transmission and prevention of COVID-19 are regarded as the most critical and effective control measures. Therefore, the purpose of this study was to assess the knowledge of, attitude to along with precautionary practices related to COVID-19 adopted by the people of the city of Kolkata, the capital of West Bengal. Methods: A cross-sectional survey was conducted by the interview method through a telephone conversation-based study from July to October 2020. The responses (n=321) were collected using a non-random convenience sampling method. All data were analysed through SPSS software (Ver. 27). Results: A total of 321 participants were included in the present study. Gender, education, and occupation-wise, statistically significant mean knowledge, practices, and overall score differences were found (p<0.001 and <0.05). People without literacy were found to had lesser knowledge (35.1%) and adopted fewer preventive practices and precautionary measures (32.4%). This section also scored lower in overall scores (48.6%) than others. Males scored better in terms of knowledge and practices compared to females; statistically, the gender-wise association was found to be significant (p<0.001 and<0.05). Conclusions: The present study demonstrates a moderate level of knowledge and a significantly high practice (41.4% and 60.7%) about COVID-19 among the study participants. Males have higher knowledge and adopted more preventive practices and precautions than females, and the overall score is high in respect of males as compared to females.